As crises finais dos modos de produção - Tiago Teixeira Gomes (2021)
Past modes of production are configured as important keys to knowledge and analysis of historical development and the division of labor carried out by humanity, which culminated in the emergence of the first global production mode in history. The currents of thought that debated and debate capitalism in history defended: its eternity, its transition and its finite process. In the development of this work, the crisis-transition processes of past modes of production, as well as the theories that defined capitalism as a mode of production, constitute important tools for analyzing the current capitalist society. The rational destructive limit imposed by capital on humanity, represented by its accumulation and the division of labor under it, tends to present risks for the maintenance of the system and of humanity itself. Thus, post-capitalism is not representative of a more redistributive capitalist society or a new, more humanistic and collective societal configuration. Its maintenance devices lead to a deteriorating system, with symptoms of barbarism against humanity. The first global mode of production in history presents risks for the continuity of humanity.